SCREENING FOR RESISTANCE TO CUCUMBER MOSAIC CUCUMOVIRUS IN CHILLI PEPPER - M. Ashfaq; S. Iqbal; T. Mukhtar; H. Shah (Journal of Animal and Plant Sciences, 2014)
Cucumber mosaic cucumovirus (CMV) is destructive pathogen with widest host range, infecting more than 100 botanical families comprising more than 500 genera and 1300 plant species. Chilli pepper is a significant cash crop of Pakistan among vegetable grown. The identification of genetic resistance to CMV in Pakistan (CMV chilli isolate) in chilli pepper is of economic importance. Thus, 40 Chilli pepper genotypes, both local and imported, were evaluated by mechanical/ manual virus inoculation and resistance to CMV chilli isolate was examined by visual observations and enzyme-linked immunosorbent assay (DAS-ELISA). On the basis of 0-5 disease rating scale and ELISA, nine genotypes viz., C-2, CV-2, CV-5, BSS-269, PGRI, M-2001, CM-2001, M-97 and CP-328 were remained free of infection and catalogued as highly resistant. Rest of the genotypes exhibited characteristic symptoms like mosaic, mottling, leaf curling and reduced leaf size depending upon tested genotypes. Among these genotypes, five were categorized as resistant, seven as moderately resistant, eight as moderately susceptible and 11 as susceptible.  These resistant and moderate resistant genotypes could be used by farmers in cultivation under integrated production systems and by breeders in developing new chilli pepper hybrid resistant genotypes to CMV.
Keywords: Chilli pepper; Cucumber mosaic virus; resistant; ELISA